Enhancing Writing Skill with Gamified Learning: Developing Sentence and Vocabulary for Fifth Grade Students at Sri Aman Suksa School - Keyti Endhita; Henny Mardiah (Universitas Islam Negeri Palopo, 2025)
This study is aimed at examining the effectiveness of gamified learning for enhancing English writing skills, particularly focusing on sentence construction and vocabulary enrichment, towards the fifth-grade students at Sri Aman Suksa School, Thailand. The research utilized a quantitative methodology incorporating pre-test and post-test frameworks. There were 25 students engaged in the research, undertaking a writing pre-test prior to the treatment and a post-test subsequent to the implementation of gamified learning activities. To address the abnormal distribution in the post-test data, the Wilcoxon Signed Rank Test was utilised to assess the significant difference between pre-test and post-test outcomes. The results indicated that students' preliminary writing proficiency was average, characterized by recurrent grammatical inaccuracies and restricted vocabulary utilization. Following the implementation of gamified learning activities, their post-test performance improved by 19 points on average (from 53.44 to 72.44), a statistically significant enhancement (p = 0.000). The effect size analysis revealed a Cohen’s d value of 1.15, indicating a substantial and significant effect. The findings indicate that gamified learning fostered engaging and motivating learning, allowing students to formulate more precise sentences and effectively broaden their vocabulary. In conclusion, gamified learning is an effective educational approach for enhancing writing skills in primary-level English as a Foreign Language (EFL) setting. It underscores the potential of a gamified learning approach to improve students’ writing skills. Furthermore, it provides significant implications for English language instruction at the primary education level.